The use of conjunctival swab samples for PCR screening for visceral leishmaniasis in vaccinated dogs - Leite,Rodrigo Souza (2011)
The polymerase chain reaction (PCR) has been shown to provide a rapid and sensitive technique for Leishmania detection. The aim of this study was to evaluate the technique of noninvasive conjunctival swabs (CS) as a sampling method for molecular screening for visceral leishmaniasis (VL) in a group of 42 police dogs, all of them vaccinated against VL, and to compare the results with those obtained by serological tests. The serological assays were performed independently by three laboratories. Laboratories 1 and 2 were private laboratories and laboratory 3 was the National Reference Laboratory. The first serological screening performed by laboratory 1 showed 15 reactive dogs and 4 indeterminate. Laboratory 2 confirmed only 3 reactive dogs and 2 indeterminate. Laboratory 3 confirmed 7 reactive dogs and 3 indeterminate. The PCR diagnosis using the CS procedure was performed on all 42 animals and was able to detect Leishmania DNA in 17 dogs. The PCR assay confirmed all the cases that were simultaneously reactive in the serological tests by two laboratories. The results showed that the CS technique was a sensitive and practical method for sample collection, thus allowing reliable diagnostic tests through PCR.